CAD-CAM vs. conventional denture bases: a systematic review with network meta-analysis of in vitro studies comparing strength, hardness, toughness, and elastic properties - Rohit Kunnath Menon; Hui Xin Yew; Benjamin Chen Tze Wei; Farah Mohammed Ramadan; Afraa Ibrahim Soliman; Sajesh Veettil (Frontiers in Dental Medicine)
BackgroundScientific evidence from in vitro studies comparing the mechanical properties of dentures fabricated with computer-aided design-computer-aided manufacturing (CAD-CAM) and conventional techniques is inconclusive. This systematic review with meta-analysis was conducted to analyze the current evidence comparing the mechanical properties of conventional and digitally fabricated denture bases from in vitro studies.Materials and methodsA systematic search was conducted in PubMed, Scopus, and Medline for in vitro studies from inception until 16 January 2025. The review had been registered with the International Prospective Register of Systematic Reviews PROSPERO: CRD42024531425). A network meta-analysis compared conventional and digitally fabricated denture bases’ flexural strength, hardness, flexural modulus, elastic modulus, impact strength, fracture toughness, yield point, and toughness. Risk of bias was assessed by using RoBDEMAT (RoB 2.0).Results4,994 articles were identified, 966 duplicates were removed, 3,971 were excluded by title and abstract screening, 57 were assessed by full-text reading, and 42 were included in the quantitative synthesis. As per the sensitivity analysis performed after excluding low-quality studies, the network meta-analysis results indicate that milled digital denture bases exhibit higher flexural strength [SMD = 2.13 (95% CI: 0.21, 4.05)] compared to 3D-printed digitally fabricated denture bases. Bias incorporated from higher values from one study diminishes the quality of evidence for impact strength and flexural modulus.ConclusionMilled digital denture bases exhibit superior flexural strength to 3D-printed and conventionally fabricated denture bases under laboratory conditions. High-quality in vitro studies are recommended to provide conclusive evidence for other mechanical properties.Systematic Review RegistrationPROSPERO CRD42024531425.